ROLE OF ION PAIRS AND ACTIVITY IN ESTIMATION OF IONIC STRENGTH FROM ELECTRICAL CONDUCTIVITY OF IRRIGATION WATER - K. S. Rajab,; A. O. Esmail, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was carried out in Erbil governorate, Iraq during 2020 to estimate the regression relations between the ionic strength of 354 water samples and their electrical conductivity then influence of correcting ion pairs and activity on this relation. Results indicated that electrical conductivity regards as an accurate measure of ionic strength for irrigation water. Correcting ion pairs plus activity had a great effect on the regression values between ionic strength values and electrical conductivity of the studied water samples. Highly significant correlation coefficient was recorded between ionic strength and electrical conductivity before correction and after correcting ion pairs and ion pairs plus activity with the correlation coefficient values of (r= 0.99**, 0.93** and 0.97**) respectively. Correcting ion pairs and ion pairs plus activity caused a decrease in the slope of the regression from 0.0157 to 0.0104 and 0.0047 respectively. Neglecting intercept values from the regression line caused an increase in the slope of regression relation to 0.0112 and 0.0058 for correcting ion pairs and ion pairs plus activity respectively.